Pengawasan Manajemen Risiko dan Financial Distress dalam Agency Theory - Mokoginta, Dirgantara Dahana; Agung, Tauchita Ramadhania (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
This study aims to examine the effect of the characteristics of the risk committee as the supervisor of risk management activities on financial distress. The characteristics in question are the number of members, gender diversity, meeting attendance ratio, financial expertise of members, and independence of members. The analytical tool used is logistic regression. The results showed that the number of members, meeting attendance ratio, and independence had no significant effect on financial distress. Gender diversity has a negative effect on financial distress, and financial expertise has a positive effect on financial distress. The conclusion of this study is that women are better at monitoring and managing risk, so they can prevent financial distress, while financial expertise is not a relevant skill for monitoring and managing risk in non-financial companies. Keywords: Financial Distress; Risk Management; Agency Theory.